Manajemen Pengelolaan Bank Sampah di Kota Bekasi - Elvira Suryani (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2016)
Increasing population , and an increase in consumption patterns of the various products imposes a buildup of waste from households . Garbage is usually dumped into landfills to be piled up. To overcome this problem the government implements policies and breakthrough "Social Engginering " with using Garbage Bank system , from trash to save money. This activity is very effective in reducing the amount of garbage , if supported by good waste management